Kesantunan Berbahasa dalam Film Jalan Yang Jauh, Jangan Lupa Pulang - Oktarina, Santi; Masbie, Fidhalia Trinanda (GERAM (Gerakan Aktif Menulis), 2025)
The purpose of this study is to determine the politeness of language in the film Jalan Yang Jauh, Jangan Lupa Pulang. In this study, there are 6 maxims in politeness of language, namely the maxim of wisdom, the maxim of generosity, the maxim of appreciation, the maxim of simplicity, the maxim of agreement and the maxim of sympathy. The data of this study uses a qualitative data method collected by analyzing the maxims of politeness of language in the film Jalan Yang Jauh Jangan Lupa Pulang. The results of this study are that researchers have found several speech data in the film Jalan Yang Jauh Jangan Lupa Pulang which contain politeness in language including verbal politeness and non-verbal politeness. The results of this study also show that the film is worthy to be used as research material and viewing material because the speech in the film contains many politeness values in communication, as we know that polite speech is very important to be applied in everyday life, especially in the current era.